2012
DOI: 10.3846/16111699.2011.620159
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Management Commitment to Service Quality on Job Embeddedness and Performance Outcomes

Abstract: Abstract. The purpose of this study is to develop and test a conceptual model that examines job embeddedness as a partial mediator of the impact of management commitment to service quality on service recovery performance and extra-role customer service. Training, empowerment, and rewards are regarded as the three important indicators of management commitment to service quality. Data were obtained from a sample of fulltime frontline hotel employees with a time lag of one week in Romania. The results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 58 publications
4
60
0
2
Order By: Relevance
“…This view is supported by both the original authors and the findings of subsequent research (e.g. Burton, Holtom, Sablynski, Mitchell & Lee, 2010;Karatepe & Karadas, 2012).Unfortunately, the preference for a composite or global measure has obscured more meaningful analysis of individual factors. The "mean of means" approach (Mitchell et al, :1111 obfuscates divergences and contradictions between factors through the application of central tendency formulae.…”
Section: Dimensionality Of Job Embeddednessmentioning
confidence: 79%
“…This view is supported by both the original authors and the findings of subsequent research (e.g. Burton, Holtom, Sablynski, Mitchell & Lee, 2010;Karatepe & Karadas, 2012).Unfortunately, the preference for a composite or global measure has obscured more meaningful analysis of individual factors. The "mean of means" approach (Mitchell et al, :1111 obfuscates divergences and contradictions between factors through the application of central tendency formulae.…”
Section: Dimensionality Of Job Embeddednessmentioning
confidence: 79%
“…Consistent with previous and recent studies (e.g., Babakus et al 2003;Karatepe and Karadas 2012;Feldman 2010, 2011), age, gender, education, organizational tenure, and marital status are treated as control variables, because they may be significantly related to study variables and confound the relationships demonstrated in the model.…”
Section: Research Modelmentioning
confidence: 95%
“…Karatepe and Karadas 2012;Ng and Feldman 2010). I have included these performance outcomes in the research model to understand whether job embeddedness simultaneously leads to service recovery performance and job performance.…”
Section: Purposementioning
confidence: 99%
“…Karatepe, & Karadas, 2012Lau, 2014. None of studies have focused on the CSQ from employee perspective.…”
mentioning
confidence: 99%